The problem of accuracy in dietary surveys. Analysis of the over 65 UK National Diet and Nutrition Survey. Issue 8 (1st August 2000) - Cook, Adrian; Pryer, Jane; Shetty, Prakash
Abstract : STUDY OBJECTIVE: To investigate the prevalence and nature of low energy reporting in a dietary survey of British adults over 65 years of age. DESIGN: Randomly selected cross sectional sample of 2060 British adults over 65 years. Four day weighed food diaries and questionnaires on health, lifestyle and socioeconomic characteristics. SETTING: Great Britain. PARTICIPANTS: 539 women and 558 men over 65 years who were free living and completed four day food diaries. MAIN RESULTS: A high proportion of men and women were classified as low energy reporters (LERs). Reported consumption of full fat dairy products, sugar and sweet foods, and alcoholic drinks differed most between LERs and non-LERs. Among LERs, reported protein and starch intakes were higher, fat, sugar and alcohol intakes were lower. LERs of either sex were more likely to be obese, male LERs were also more likely to belong to the manual social classes. CONCLUSIONS: The high level of low energy reporting probably resulted from a coalescence of factors such as the weighed diary methodology and a reluctance to report consumption of unhealthy foods. The use of validatory biomarkers such as doubly labelled water needs to be more widespread.